Aksesibilitas Petani Bawang Merah Terhadap Lembaga Keuangan Mikro Sebagai Sumber Pembiayaan - Rahayu, Lestari (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
Microfinance institutions (MFIs) is an institution conducting the provision of financial services to micro and small entrepreneurs including shallot farmers. This study aims to determine the accessiÂbility and the influencing factors of farmers decisions in determining the source of financing for shallot business sustainability. The study was conducted in Bantul as the centre production of shallot in DIY Two hundred and five of farmers (205 persons) as microfinance client taken randomly, were interviewed and observed in collecting primary data, and then analyzed using Multinomial Logit Model. Farmers group is the microfinance institution that the most accessible for farmers to access shortÂterm credit scheme (seasonal). TheÂ farmers can defer the payment to the next season in case the crop failure, while the farmers perceive that the administrative procedures is simple. Tne education level of farmers, the farming experience, the number of family members, the frequency of credit, the farmers perception about MFI services, the total income, and the amount of credits are the factors that influence the decisions of farmers in the selection of the MFI as source of business finance.